(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines folklore as a component of traditional culture and its role in the formation of the ethnocultural code of representatives of an ethnic group. In particular, it is emphasized that language as an important element of the ethnocultural code occupies a certain place in the social life of ethnic groups, and examples of folk oral creativity are the leading factor in its propaganda. Bayushki, proverbs and sayings, songs and epics are examples of folklore, their place in traditional culture and in the formation and development of the cultural code of representatives of an ethnic group is discussed. The issues of the importance of traditional culture in the process of nation formation are also analyzed.